Impact of stirrer rotational speed on liquid circulation in a rectangular vessel – a study applying DPIV - Ligus Grzegorz; Wasilewski Marek (E3S Web of Conferences, 2018)
This paper contains the results of experimental study concerned with liquid mixing process using a stirrer located in a rectangular vessel. The current study applied Digital Particle Image Velocimetry technique (DPIV). On the basis of non-invasive measurements, velocity vector profiles were determined with regard to the velocity of the mixing process, and they were subsequently applied for identification and assessment of liquid circulation in a vessel. The correlation between the rotational speed of the stirrer and fluctuations and directions of the liquid flow velocity were determined. This paper focuses on the assessment of the mixing intensity resulting from the rectangular geometry of the vessel. The study proposes and develops a dependence between the shape of the velocity profile of the circulating liquid and the intensity of the mixing process. The study demonstrates the existence of suitable conditions for performing mixing processes in rectangular vessels.